Infection Control awareness among Nursing students: Descriptive Insights from Ongoing Clinical Orientations in Odisha - Jagadish Nayak; N Premlata Devi; Sathish Rajamani (International Journal of Evidence Based Nursing And Practices, 2025)
Background: Effective infection control practices are critical in preventing healthcare-associated infections (HAIs). Aim: This study aimed to assess the awareness regarding effective infection control measures among student nurses undertaking their initial clinical orientations at Hospitals. Method: The study accepted 64 respondents from II-year BSc Nursing, sampled in clusters from selected Hospitals, Odisha. Results: The students yielded a mean awareness score of 0.69, categorized as Good. A comparison revealed that female students consistently outperformed males in all sanitary parameters, with the highest awareness observed in contamination risks (83%). Discussion: The findings indicate significant knowledge on nosocomial infections, precautionary standards, and contamination risks among nursing students, with room for improvements in specific domains as such hand hygiene (66.3%) and the use of alcohol-based rubs (59.1%) that require attention. The study further recommends evidence-based training and simulation-based learning to bridge knowledge gaps.
Keywords: Awareness; Nosocomial infections; infection control; nursing students